2011
DOI: 10.1038/ejhg.2011.94
|View full text |Cite
|
Sign up to set email alerts
|

Are the kids really all right? Direct-to-consumer genetic testing in children: are company policies clashing with professional norms?

Abstract: The genetic testing of minors within the direct-to-consumer (DTC) genetic testing (GT) context has been given relatively little attention. The issue of testing healthy children for diseases that would only develop in adulthood raises many important ethical, legal and social issues. As genetic testing is now available outside of the traditional health care system, often without even the intermediate of a health care professional, we surveyed 37 DTC GT companies regarding their policies for testing in children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…Three companies would consider testing if it was requested by a minor. 51 Finally, there is no consistency regarding the information provided on DTC GT websites regarding consent for testing. Information on DTC GT websites might not be balanced with regard to how they present risks and benefits.…”
Section: Direct-to-consumer Testingmentioning
confidence: 99%
“…Three companies would consider testing if it was requested by a minor. 51 Finally, there is no consistency regarding the information provided on DTC GT websites regarding consent for testing. Information on DTC GT websites might not be balanced with regard to how they present risks and benefits.…”
Section: Direct-to-consumer Testingmentioning
confidence: 99%
“…Although pharmacogenetics was not discussed in the ESHG statement, there are potential problems for inclusion in DTC services 19 if, for example, the consumer is then tempted to adjust their dose of prescribed medicine without seeking medical advice. Testing of samples from minors (including carrier testing) and third parties (who have not consented) should not be permitted but there is evidence that some DTC services are including genetic testing in minors, 20 contradicting established professional guidelines, including those of the ESHG.…”
Section: The Scope Of Dtc Genetic Testingmentioning
confidence: 99%
“…[5][6][7][8][9] First, informed consent may be compromised by lack of provision of appropriate facts. 9 Second, confidentiality may be breached through integration of online social networking opportunities into the websites of DTC-GT companies which promote sharing of personal genomic information 7 and, although this may facilitate collaboration between clients and researchers, the consequences of these potential confidentiality breaches are difficult to predict.…”
Section: Introductionmentioning
confidence: 99%
“…8 Third, although most DTC-GT companies maintain that their services are not intended to attract minors, testing in minors continues to occur. 5,6 Although there is a body of literature regarding DTC-GT, observational studies are limited. Some case studies have reported DTC-GT results with apparent clinical utility [10][11][12] and other studies report results with no clinical utility.…”
Section: Introductionmentioning
confidence: 99%